1989
DOI: 10.1037/0021-9010.74.3.424
|View full text |Cite
|
Sign up to set email alerts
|

A work values approach to corporate culture: A field test of the value congruence process and its relationship to individual outcomes.

Abstract: The purported advantage of a strong corporate culture presumes that positive outcomes result when peoples' values are congruent with those of others. This was tested by using a design that controlled for artifacts in prior studies. Participants, 191 production workers, their supervisors (N = 17), and 13 managers at a large industrial products plant, completed questionnaires containing measures of job satisfaction, organizational commitment, and work values. Responses were later matched with the attendance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
467
1
18

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(504 citation statements)
references
References 39 publications
18
467
1
18
Order By: Relevance
“…In the above cited studies, the relationship between superior-subordinate congruence and performance was found to be positive. On the other hand, Meglino, Ravlin & Adkins (1989) found a negative association between superior subordinate congruence and the rated quality and quantity of the performance of the subordinate. The results of Meglino et al (1989) clearly contradict findings in other studies.…”
Section: Superior-subordinate Congruence As a Possible Extension Of Tmentioning
confidence: 83%
See 1 more Smart Citation
“…In the above cited studies, the relationship between superior-subordinate congruence and performance was found to be positive. On the other hand, Meglino, Ravlin & Adkins (1989) found a negative association between superior subordinate congruence and the rated quality and quantity of the performance of the subordinate. The results of Meglino et al (1989) clearly contradict findings in other studies.…”
Section: Superior-subordinate Congruence As a Possible Extension Of Tmentioning
confidence: 83%
“…On the other hand, Meglino, Ravlin & Adkins (1989) found a negative association between superior subordinate congruence and the rated quality and quantity of the performance of the subordinate. The results of Meglino et al (1989) clearly contradict findings in other studies. Further research ought to be conducted to resolve this apparent controversy.…”
Section: Superior-subordinate Congruence As a Possible Extension Of Tmentioning
confidence: 83%
“…In some organisational literature there is a good deal of emphasis on the value of positive employee attitudes and a sense of alignment with the organisation's core values (Meglino, Ravlin, & Adkins, 1989;Posner, 1992;Syrett et al, 1997). The sense of shared meaning with colleagues and emotional attachment to core values and philosophies has been linked to positive work attitudes and enhanced work performance.…”
Section: In Conclusion: the Clinical Governance Of The Soulmentioning
confidence: 99%
“…A great deal of scholarship supports the importance of employee value congruence with supervisors, leaders and organizational culture, and links value congruence to various outcomes including satisfaction, commitment, emotional engagement, trust and performance (Avolio 2000;Chatman 1991;Jung and Avoilo 2000;Kirkpatrick and Locke 1996;Meglino et al 1989;Shamir et al 1993). Collectively, research shows that value congruence makes shared meaning and coordinated behavior more likely.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%